2017
DOI: 10.1038/s41598-017-01429-5
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine degradation through PEI-copper nanoparticles deposited onto montmorillonite and sand

Abstract: We present the synthesis of new composite materials based on copper nanoparticles (Cu NPs) deposited onto montmorillonite (MK10) and quartz sand, for degradation of atrazine, in the context of an advanced oxidation process (AOP). The synthesis involves a first step in which polyethylenimine (PEI) capped Cu NPs (PEI_Cu NPs) are prepared, and then deposited onto, separately, MK10 and sand, through a solvent impregnation method. The resulting products are characterized in detail; the copper is found to exist as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…In the present study, the marked CAT inhibition in M30‐NP treatments can be explained by a higher ROS formation overloading the antioxidant system. Reactive oxygen species formation may be caused by the high reactivity of Cu–montmorillonite associations, which are able to break down organic compounds and are known to be more reactive than Cu–kaolin (Khanikar & Bhattacharyya, 2013) or Cu–sand associations (Kalidhasan et al, 2017). For example, Cu–montmorillonite associations can cause a high degradation rate of atrazine through the activation of molecular oxygen and the subsequent hydroxyl radical formation (Hong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the marked CAT inhibition in M30‐NP treatments can be explained by a higher ROS formation overloading the antioxidant system. Reactive oxygen species formation may be caused by the high reactivity of Cu–montmorillonite associations, which are able to break down organic compounds and are known to be more reactive than Cu–kaolin (Khanikar & Bhattacharyya, 2013) or Cu–sand associations (Kalidhasan et al, 2017). For example, Cu–montmorillonite associations can cause a high degradation rate of atrazine through the activation of molecular oxygen and the subsequent hydroxyl radical formation (Hong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we exposed the standard test organism Folsomia candida to CuO-NPs and CuCl 2 in Organisation for Economic Co-operation and Development (OECD) soils containing either kaolin or montmorillonite as the clay fraction. Both clays are either exemplary for two-or three-layer clay minerals and are widely used, for example kaolin in OECD soil and Montmorillonite K10 in different catalytic (Kalidhasan et al, 2017;Khanikar & Bhattacharyya, 2013) and ecotoxicological studies (Gupta et al, 2016(Gupta et al, , 2017Kansara et al, 2019). We compared the impact of these soils on the toxicity of the Cu substances to the survival, reproduction, growth, molting, and biochemical responses of F. candida.…”
Section: Introductionmentioning
confidence: 99%
“…The second group of chemolytic agents tested here were strong oxidation agents—copper nanoparticles with H 2 O 2 [ 26 ] and Fenton reaction (pH 2–4, Fe 2+ , H 2 O 2 ) [ 27 ]—both of which have been shown highly effective in degrading organic matter in complex matrices. These agents were applied to check their ability to degrade the organic substances and thus weaken or disintegrate the stone.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanistic studies of adsorption and oxidation have revealed the contribution of atrazine adsorption by Cu as an active catalyst via coordination bonding with nitrogen from the atrazine structure, yielding a significant reduction in the chemical oxygen demand of the treated solution. Cu 2 O and CuO identified on the surface are recognized as the redox-active species within the pores, layers, and outside of the montmorillonite surfaces [ 189 ]. In an ionic form, Cu 2+ -immobilized aluminum-pillared montmorillonite (Cu/Al-PILM) showed a capability for use in Fenton and photo-Fenton treatments of RO16 [ 190 ].…”
Section: Clay-supported Metal Oxide In Aopsmentioning
confidence: 99%